Gênero e feminismo para cristãos capixabas: um estudo de representações sociais. - Moreira, Ana Carolina Caetano Tavares (2020)
The gender thematic has been a widely discussed phenomenon in several studies in humanities and social sciences areas over the past few years and, recently, its debate has increased in social media and networks in Brazilian scenario, reaching more directl